2020
DOI: 10.1097/md.0000000000020477
|View full text |Cite
|
Sign up to set email alerts
|

Interbody fusion in degenerative lumbar spinal stenosis with additional posterolateral fusion using Escherichia coli-derived bone morphogenetic protein-2

Abstract: This case series investigated the efficacy and optimal dose of Escherichia coli-derived bone morphogenetic protein-2 (E.BMP-2) as a bone graft substitute for additional posterolateral spinal fusion, accompanying interbody fusion procedures, for treating lumbar degenerative spinal stenosis. This study focused on the optimal dose for each segment and the efficacy of E.BMP-2 as a substitute for autogenous iliac bone graft. Ten patients were enrolled from January 2015 to December 2015, and underwent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In previous studies using BMP-2 in spine fusion surgery, a solid union was observed within a relatively short follow-up period after surgery. 10 11 12 22) Likewise, 15 of 21 segments (71.4%) showed solid fusion at 3 months after surgery and 19 of 21 segments (90.4%) at 6 months after surgery in the present study. This is considered to be a great advantage of BMP-2.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In previous studies using BMP-2 in spine fusion surgery, a solid union was observed within a relatively short follow-up period after surgery. 10 11 12 22) Likewise, 15 of 21 segments (71.4%) showed solid fusion at 3 months after surgery and 19 of 21 segments (90.4%) at 6 months after surgery in the present study. This is considered to be a great advantage of BMP-2.…”
Section: Discussionsupporting
confidence: 61%
“…In a clinical study by Cho et al, 11) lumbar posterolateral fusion (PLF) using 6 mg of E.BMP-2 per level bilaterally showed a 100% fusion rate 24 weeks after surgery. Choi et al 10) reported a 100% PLF rate using 2.5 mg of E.BMP-2 per level unilaterally in addition to lumbar interbody fusion, and a solid fusion was observed at a mean of 4.5 months after surgery. Son et al 12) compared grafting autologous IBG and E.BMP-2 when performing lumbar interbody fusion and an additional one-sided PLF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorbable collagen sponge (ACS), hydroxyapatite (HA), or beta‐tricalcium phosphate (β‐TCP) can be used as carriers. Among them, HA carrier used with E‐rhBMP‐2 for posterolateral fusion achieved 100% fusion rate within 6 months 20,21 . HA has good osteoconductivity and biocompatibility, but the absorption rate is low and has difficulty in further bone remodeling 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, HA carrier used with E‐rhBMP‐2 for posterolateral fusion achieved 100% fusion rate within 6 months. 20 , 21 HA has good osteoconductivity and biocompatibility, but the absorption rate is low and has difficulty in further bone remodeling. 22 In contrast, β‐TCP is completely resorbable and has high affinity to rhBMP‐2.…”
Section: Introductionmentioning
confidence: 99%